Persepsi Perilaku Caring oleh Perawat Berhubungan dengan Stres Kerja - Roisul Umam (Jurnal Keperawatan Silampari, 2020)
This study aims to analyze the relationship between nurses' job stress and perceptions of caring behavior. The method in this study used a correlation analytic research design with a cross-sectional approach. The analysis results using the Spearman correlation test obtained the calculated r-value of 0.876 and a significance value of Sig. (2-tailed) of 0.001 (<0.05). In conclusion, nurses' work stress has a significant relationship with the perception of caring behavior at RSI Sakinah Mojokerto. Keywords: Nurse, Perceptions of Caring Behavior, Stress